2016
DOI: 10.5005/jp-journals-10005-1356
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Association between Breastfeeding Duration, Facial Profile, Occlusion, and Spacing: A Cross-sectional Study

Abstract: Introduction: This cross-sectional retrospective study was designed to assess the relationships among breastfeeding duration, nonnutritive sucking habits, convex facial profile, nonspaced dentition, and distoclusion in the deciduous dentition.Materials and methods: A sample of 415 children (228 males, 187 females) aged 4 to 6 years from a mixed Indian population was clinically examined by two orthodontists. Information about breastfeeding duration and nonnutritive sucking habits was obtained by written questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…Regarding dental and skeletal class II malocclusion, despite some discrepancies the majority of studies considered that breastfeeding is associated with less distocclusion in both primary 13, 14, 32 and mixed dentition 31 . However, other authors 19, 30, 33 found no relationship between breastfeeding and class II in mixed and primary dentition, respectively.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Regarding dental and skeletal class II malocclusion, despite some discrepancies the majority of studies considered that breastfeeding is associated with less distocclusion in both primary 13, 14, 32 and mixed dentition 31 . However, other authors 19, 30, 33 found no relationship between breastfeeding and class II in mixed and primary dentition, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…and Agarwal et al . 13, 14, 32, 33 investigated the same association in primary dentition. The relationship between breastfeeding and the development of occlusion/malocclusion was analyzed in nine studies, all in primary dentition 57, 1012, 18, 34, 35 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Breastfeeding can be seen as a natural orthopaedic appliance that promotes good craniofacial development, as the movements produced by the tongue and mandible during the suction of breast milk stimulate a better maxillary and mandibular growth (2). Furthermore, for the child to obtain milk during breastfeeding the stimulation of tongue and peribuccal muscles is required, whereas less effort is required for bottle-fed children to obtain milk, therefore causing less stimulation of the orofacial structures (3).…”
Section: Introductionmentioning
confidence: 99%